Multi-network composite hydrogel inhibitor as well as preparation method and application thereof
By using multi-network composite hydrogel resistors, using highly absorbent resins, film-forming stabilizers and clay materials to form film-like protective layers, solving the problems of low resistance efficiency and environmental pollution of existing magnesium chloride resistors, and achieving efficient and environmentally friendly underground spontaneous combustion prevention and control effects of coal mines.
Patent Information
- Application Number
- CN202510206285.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-15
AI Technical Summary
The magnesium chloride inhibitor used in existing coal mines has problems such as low resistance efficiency, easy loss, damage equipment and endangering workers' health, and after spraying, the chloride ions in the discharged wastewater from the underground will exceed the standard.
A multi-network composite hydrogel barrier agent is used, which consists of a highly absorbent resin, a film-forming stabilizer, a cationic clay and/or anionic clay. Through specific proportions and combinations, a film-like protective layer with high water absorption and good adhesion is formed.
It achieves high resistance rate and long resistance life, reduces the use of raw materials and labor costs, adapts to the underground water quality of different mining areas, and is green and environmentally friendly, and does not introduce foreign chloride ions.
Smart Images

Figure CN119819210A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inhibitors, and in particular to a multi-network composite hydrogel inhibitor and a preparation method and application thereof. Background Art
[0002] Spontaneous combustion of coal not only results in the loss of a large amount of valuable coal resources, but also produces toxic and harmful gases. Serious fire accidents may lead to secondary disasters such as gas and coal dust explosions. Inhibitors have become an effective means of preventing spontaneous combustion in coal mines due to their advantages of easy spraying, low price and good inhibitory effect.
[0003] At present, most of the inhibitors sprayed in coal mines are magnesium chloride inhibitors, which have become the most commonly used inhibitors due to their water absorption and low price. However, magnesium chloride inhibitors will introduce chloride ions, which will damage underground equipment to a certain extent and endanger the health of workers. At the same time, this type of inhibitor is easy to lose after spraying, and the inhibition efficiency is low. After spraying, the chloride ion content in the underground wastewater will exceed the standard.
[0004] Therefore, it is urgent to develop an inhibitor with high inhibition efficiency and without introducing foreign chloride ions, so as to achieve the purpose of preventing and controlling spontaneous combustion in coal mines. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.
[0006] To this end, the embodiments of the present invention provide a multi-network composite hydrogel inhibitor and a preparation method and application thereof.
[0007] In the first aspect, the present invention provides a multi-network composite hydrogel inhibitor, characterized in that it comprises:
[0008] Highly water-absorbent resin, the mass proportion of the highly water-absorbent resin in the inhibitor is 0.3% to 0.8%;
[0009] A film-forming stabilizer, wherein the mass proportion of the film-forming stabilizer in the inhibitor is 0.05% to 0.2%;
[0010] Cationic clay and / or anionic clay, wherein the mass proportion of the cationic clay in the inhibitor is 0.6% to 2%, and the mass proportion of the anionic clay in the inhibitor is 0.6% to 2%.
[0011] Furthermore, it also includes an anti-hard water agent, and the mass proportion of the anti-hard water agent in the inhibitor is less than 0.1%.
[0012] Furthermore, the anti-hard water agent includes one or more of 2-acrylamide-2-methylpropanesulfonate sodium, 3-(N-morpholine)-propanesulfonate sodium and polymers thereof.
[0013] Furthermore, the super absorbent resin includes one or more of polyacrylic acid, sodium polyacrylate, and polypropylene alcohol.
[0014] Furthermore, the film-forming stabilizer includes one or more of anionic polyacrylamide, cationic polyacrylamide, and nonionic polyacrylamide.
[0015] Furthermore, the cationic clay includes one or more of sodium bentonite, calcium bentonite, and organic bentonite.
[0016] Furthermore, the anionic clay includes one or both of aluminum-magnesium layered double metal hydroxides and hydrophilically modified aluminum-magnesium layered double metal hydroxides.
[0017] In a second aspect, the present invention provides a method for preparing the inhibitor provided in the first aspect, comprising the following steps:
[0018] Weigh the solid materials respectively according to the usage ratio, and mix the solid materials evenly to obtain a mixture;
[0019] The mixture is added into deionized water or hard water containing an anti-hard water agent, stirred until completely dispersed, and then allowed to stand to obtain a multi-network composite hydrogel inhibitor.
[0020] Furthermore, the solid material includes at least one of cationic clay and anionic clay, a highly absorbent resin and a film-forming stabilizer.
[0021] In a third aspect, the present invention proposes the use of the inhibitor proposed in the first aspect or the inhibitor prepared by the method proposed in the second aspect in the prevention and control of spontaneous combustion in coal mines.
[0022] Compared with the prior art, the beneficial effects of the present invention are:
[0023] The inhibitor of the present invention has a high inhibition rate, a long inhibition life, and better adhesion. After spraying, it forms a film-like protective layer on the surface of the coal seam. At the same time, the performance of the inhibitor is evaluated from a new perspective through a cone calorimeter, which shows that the inhibitor of the present invention requires a long ignition time, has a low smoke production per unit time, and a low average heat release rate.
[0024] The solid material content of the inhibitor used in the invention is small, which can greatly reduce the amount of raw materials used. At the same time, when used underground in coal mines, it can greatly save labor costs, is suitable for underground water quality in different mining areas, and ensures the inhibitory effect.
[0025] The inhibitor of the invention is green and environmentally friendly, does not introduce harmful substances such as external chloride ions, and does not cause a burden on underground water treatment in coal mines after spraying. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0027] Figure 1 This is a process diagram of the preparation method of the multi-network composite hydrogel inhibitor of the present invention. DETAILED DESCRIPTION
[0028] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0029] The following describes the multi-network composite hydrogel inhibitor and its preparation method and application according to the embodiments of the present invention with reference to the accompanying drawings.
[0030] The multi-network composite hydrogel inhibitor comprises a highly absorbent resin, a film-forming stabilizer and clay, wherein the clay is cationic clay and / or anionic clay.
[0031] The super absorbent resin includes one or more of polyacrylic acid, sodium polyacrylate, and polypropylene alcohol. The super absorbent resin has a three-dimensional network structure, contains a large number of hydrophilic groups, and has strong water absorption and water retention properties.
[0032] In some embodiments, the mass proportion of the super absorbent resin in the inhibitor is 0.3% to 0.8%. The mass proportion of the super absorbent resin in the inhibitor can be 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, or a value within a range composed of any two values. The mass proportion of the super absorbent resin within a suitable range enables the composite hydrogel system to achieve the best water absorption and water retention effect, thereby improving its flame retardant and flame retardant properties; when the mass proportion of the super absorbent resin is too low, the components of the system cannot be evenly dispersed, thereby reducing the flame retardant and flame retardant properties; when the mass proportion of the super absorbent resin is too high, the system has poor fluidity, and it is easy to agglomerate during the preparation process, which makes the water absorption and water retention effect worse, thereby affecting the flame retardant and flame retardant properties.
[0033] The film-forming stabilizer includes one or more of anionic polyacrylamide, cationic polyacrylamide and nonionic polyacrylamide. The film-forming stabilizer component also has a network structure, in which some functional groups (such as amide groups) can associate with the water-absorbing resin to form hydrogen bonds, enhance the viscosity and stability of the system, and form a film-like protective layer on the surface of the coal after spraying.
[0034] In some embodiments, the mass proportion of the film-forming stabilizer in the inhibitor is 0.05% to 0.2%. The mass proportion of the film-forming stabilizer in the inhibitor can be 0.05%, 0.1%, 0.15%, 0.2%, or a value within a range composed of any two values. The mass proportion of the film-forming stabilizer within a suitable range stabilizes the viscosity of the composite hydrogel system; when the mass proportion of the film-forming stabilizer is too low, the adhesion of the inhibitor is poor and it cannot adhere to the coal wall; when the mass proportion of the film-forming stabilizer is too high, it is easy to agglomerate with the water-absorbing resin.
[0035] The cationic clay includes one or more of sodium bentonite, calcium bentonite and organic bentonite.
[0036] Cationic clay contains a large amount of aluminum, silicon and other ions. After spraying, it adheres to the surface of the coal seam to form a dense metal or non-metal oxide protective layer. Cationic clay contains a large number of hydroxyl groups in its structure and has good dispersibility in water. A large number of water molecules can be adsorbed between layers to achieve the effect of cooling and isolating oxygen.
[0037] In some embodiments, the mass proportion of cationic clay in the inhibitor is 0.6% to 2%. The mass proportion of cationic clay in the inhibitor can be 0.6%, 0.8%, 1.0%, 1.2%, 1.5%, 2%, or a value within a range composed of any two values. The mass proportion of cationic clay within a suitable range allows the composite hydrogel system to be stably dispersed, and the flame retardant and inhibitory effect is optimal; when the mass proportion of cationic clay is too low, the flame retardant and inhibitory performance is significantly reduced; when the mass proportion of cationic clay is too high, the system cannot be stably dispersed, and stratification will occur.
[0038] Anionic clay includes one or two of aluminum-magnesium layered double metal hydroxides and hydrophilically modified aluminum-magnesium layered double metal hydroxides. Anionic clay contains a large amount of metal ions such as aluminum and magnesium. After spraying, it can adhere to the surface of the coal seam to form a dense metal oxide protective layer. Anionic clay contains a large amount of hydroxide and carbonate in the intercalation layer. When heated, it will release water and carbon dioxide, thereby further achieving the effect of cooling and isolating oxygen.
[0039] In some embodiments, the mass proportion of anionic clay in the inhibitor is 0.6% to 2%. The mass proportion of anionic clay in the inhibitor can be 0.6%, 0.8%, 1.0%, 1.2%, 1.5%, 2%, or a value within a range composed of any two values. The mass proportion of anionic clay within a suitable range makes the composite hydrogel system stable and has good flame retardant and resistance performance; when the mass proportion of anionic clay is too low, the flame retardant and resistance performance is reduced; when the mass proportion of anionic clay is too high, the system cannot be stably dispersed and stratification will occur.
[0040] In some embodiments, the multi-network composite hydrogel inhibitor further includes an anti-hard water agent, and the anti-hard water agent includes one or more of 2-acrylamide-2-methylpropanesulfonate sodium, 3-(N-morpholine)-propanesulfonate sodium and polymers thereof.
[0041] The anti-hard water agent has negatively charged sulfonic acid groups, which can increase the electrostatic force between molecular chains, thereby improving the water absorption capacity and adhesion of the system; it can reduce the impact of the interaction between metal cations in the system, thereby making the system more stable in different water qualities. It is understandable that when it is necessary to configure the inhibitor underground, since the water quality of the underground mine is hard water, the anti-hard water agent is required during the configuration. When the inhibitor is configured on the ground, deionized water can be used, in which case the anti-hard water agent can be omitted.
[0042] In some embodiments, the mass proportion of the anti-hard water agent in the inhibitor is less than 0.1%. The mass proportion of the anti-hard water agent within a suitable range makes the composite hydrogel system uniform and stable, and reduces the influence of water quality on its flame retardant and flame retardant properties; when the mass proportion of the anti-hard water agent is too low, the system cannot exist stably, and obvious stratification will occur; when the mass proportion of the anti-hard water agent is too high, it will affect the water absorption and water retention effect of the water-absorbing resin, thereby reducing the flame retardant and flame retardant effect of the system.
[0043] The preparation method of multi-network composite hydrogel inhibitor is as follows: Figure 1 As shown, the following steps are included:
[0044] (a) weighing solid materials according to the usage ratio, and mixing the solid materials uniformly to obtain a mixture;
[0045] (b) adding the mixture into deionized water or hard water containing an anti-hard water agent, stirring until completely dispersed, and then standing to obtain a multi-network composite hydrogel inhibitor.
[0046] Wherein, the solid material in step (a) includes at least one of cationic clay and anionic clay, a highly absorbent resin and a film-forming stabilizer. First, a corresponding amount of each solid material is weighed according to the mass ratio, and then the solid materials are mixed evenly by a stirrer to obtain a mixture.
[0047] In step (b), the mixture is added to deionized water or hard water, stirred evenly and completely dispersed, and then allowed to stand for 24 hours to obtain a multi-network composite hydrogel inhibitor, which is pumped to a storage tank for standby use. When hard water is used, the anti-hard water agent needs to be added to the hard water and mixed evenly.
[0048] The inhibitor of the present invention has good moisture absorption and water retention performance, can adhere to the surface of the coal seam after spraying, maintain for a long time, and can form a film-like protective layer on the surface of the coal seam after drying, thereby preventing the spontaneous combustion reaction of coal and oxygen. The inhibitor of the present invention does not use chloride ions, and the amount of raw materials used is small, which can be adjusted according to the water quality conditions. The relative price is cheaper than the magnesium chloride inhibitor, and a large amount of labor costs are saved.
[0049] The present invention is described below with reference to specific examples. Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0050] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0051] Example 1
[0052] The multi-network composite hydrogel inhibitor includes a super absorbent resin, a film-forming stabilizer and a cationic clay, wherein the mass proportion of the super absorbent resin is 0.5%, the mass proportion of the film-forming stabilizer is 0.05%, the mass proportion of the cationic clay is 0.6%, and the rest is made up of water. The super absorbent resin is sodium polyacrylate, the cationic clay is sodium bentonite, the film-forming stabilizer is anionic polyacrylamide, and the water is deionized water.
[0053] The preparation method of the multi-network composite hydrogel inhibitor of this embodiment is as follows: solid materials and deionized water are weighed respectively according to the dosage ratio (mass fraction), deionized water is first added to the reactor, stirring is started, the solid materials are mixed evenly by the stirrer and then added to the reactor, stirred evenly and completely dispersed, and then allowed to stand for 24 hours to obtain the multi-network composite hydrogel inhibitor of this embodiment, which is then pumped to a storage tank for standby use.
[0054] Example 2
[0055] The multi-network composite hydrogel inhibitor includes a super absorbent resin, a film-forming stabilizer and a cationic clay, wherein the mass proportion of the super absorbent resin is 0.5%, the mass proportion of the film-forming stabilizer is 0.05%, the mass proportion of the cationic clay is 2%, and the rest is made up of water. The super absorbent resin is sodium polyacrylate, the cationic clay is sodium bentonite, the film-forming stabilizer is anionic polyacrylamide, and the water is deionized water.
[0056] The preparation method of the multi-network composite hydrogel inhibitor of this embodiment is the same as that of Example 1.
[0057] Example 3
[0058] The multi-network composite hydrogel inhibitor includes a super absorbent resin, a film-forming stabilizer and a cationic clay, wherein the mass proportion of the super absorbent resin is 0.5%, the mass proportion of the film-forming stabilizer is 0.05%, the mass proportion of the cationic clay is 1%, and the rest is made up of water. The super absorbent resin is sodium polyacrylate, the cationic clay is sodium bentonite, the film-forming stabilizer is anionic polyacrylamide, and the water is deionized water.
[0059] The preparation method of the multi-network composite hydrogel inhibitor of this embodiment is the same as that of Example 1.
[0060] Example 4
[0061] The multi-network composite hydrogel inhibitor includes a super absorbent resin, a film-forming stabilizer and anionic clay, wherein the mass proportion of the super absorbent resin is 0.5%, the mass proportion of the film-forming stabilizer is 0.05%, the mass proportion of the anionic clay is 0.6%, and the rest is made up of water. The super absorbent resin is polyacrylic acid, the anionic clay is aluminum-magnesium layered double metal hydroxide, the film-forming stabilizer is cationic polyacrylamide, and the water is deionized water.
[0062] The preparation method of the multi-network composite hydrogel inhibitor of this embodiment is the same as that of Example 1.
[0063] Example 5
[0064] The multi-network composite hydrogel inhibitor includes a super absorbent resin, a film-forming stabilizer and anionic clay, wherein the mass proportion of the super absorbent resin is 0.5%, the mass proportion of the film-forming stabilizer is 0.05%, the mass proportion of the anionic clay is 2%, and the rest is made up of water. The super absorbent resin is polyacrylic acid, the anionic clay is aluminum-magnesium layered double metal hydroxide, the film-forming stabilizer is cationic polyacrylamide, and the water is deionized water.
[0065] The preparation method of the multi-network composite hydrogel inhibitor of this embodiment is the same as that of Example 1.
[0066] Example 6
[0067] The multi-network composite hydrogel inhibitor includes a super absorbent resin, a film-forming stabilizer and anionic clay, wherein the mass proportion of the super absorbent resin is 0.5%, the mass proportion of the film-forming stabilizer is 0.05%, the mass proportion of the anionic clay is 1%, and the rest is made up of water. The super absorbent resin is polyacrylic acid, the anionic clay is aluminum-magnesium layered double metal hydroxide, the film-forming stabilizer is cationic polyacrylamide, and the water is deionized water.
[0068] The preparation method of the multi-network composite hydrogel inhibitor of this embodiment is the same as that of Example 1.
[0069] Example 7
[0070] The multi-network composite hydrogel inhibitor includes a super absorbent resin, a film-forming stabilizer and a cationic clay, wherein the mass proportion of the super absorbent resin is 0.3%, the mass proportion of the film-forming stabilizer is 0.05%, the mass proportion of the cationic clay is 1%, and the rest is made up of water. The super absorbent resin is sodium polyacrylate, the cationic clay is sodium bentonite, the film-forming stabilizer is anionic polyacrylamide, and the water is deionized water.
[0071] The preparation method of the multi-network composite hydrogel inhibitor of this embodiment is the same as that of Example 1.
[0072] Example 8
[0073] The multi-network composite hydrogel inhibitor includes a super absorbent resin, a film-forming stabilizer and a cationic clay, wherein the mass proportion of the super absorbent resin is 0.8%, the mass proportion of the film-forming stabilizer is 0.05%, the mass proportion of the cationic clay is 1%, and the rest is made up of water. The super absorbent resin is sodium polyacrylate, the cationic clay is sodium bentonite, the film-forming stabilizer is anionic polyacrylamide, and the water is deionized water.
[0074] The preparation method of the multi-network composite hydrogel inhibitor of this embodiment is the same as that of Example 1.
[0075] Example 9
[0076] The multi-network composite hydrogel inhibitor includes a super absorbent resin, a film-forming stabilizer and a cationic clay, wherein the mass proportion of the super absorbent resin is 0.5%, the mass proportion of the film-forming stabilizer is 0.1%, the mass proportion of the cationic clay is 1%, and the rest is made up of water. The super absorbent resin is sodium polyacrylate, the cationic clay is sodium bentonite, the film-forming stabilizer is anionic polyacrylamide, and the water is deionized water.
[0077] The preparation method of the multi-network composite hydrogel inhibitor of this embodiment is the same as that of Example 1.
[0078] Example 10
[0079] The multi-network composite hydrogel inhibitor includes a super absorbent resin, a film-forming stabilizer and a cationic clay, wherein the mass proportion of the super absorbent resin is 0.5%, the mass proportion of the film-forming stabilizer is 0.2%, the mass proportion of the cationic clay is 1%, and the rest is made up of water. The super absorbent resin is sodium polyacrylate, the cationic clay is sodium bentonite, the film-forming stabilizer is anionic polyacrylamide, and the water is deionized water.
[0080] The preparation method of the multi-network composite hydrogel inhibitor of this embodiment is the same as that of Example 1.
[0081] Embodiment 11
[0082] The multi-network composite hydrogel inhibitor includes a super absorbent resin, a film-forming stabilizer, a cationic clay, and an anionic clay, wherein the mass proportion of the super absorbent resin is 0.5%, the mass proportion of the film-forming stabilizer is 0.1%, the mass proportion of the cationic clay is 1%, the mass proportion of the anionic clay is 0.6%, and the rest is made up of water. The super absorbent resin is sodium polyacrylate, the cationic clay is sodium bentonite, the film-forming stabilizer is anionic polyacrylamide, the anionic clay is aluminum-magnesium layered double metal hydroxide, and the water is deionized water.
[0083] The preparation method of the multi-network composite hydrogel inhibitor of this embodiment is the same as that of Example 1.
[0084] Example 12
[0085] The multi-network composite hydrogel inhibitor includes a super absorbent resin, a film-forming stabilizer, a cationic clay, and an anionic clay, wherein the mass proportion of the super absorbent resin is 0.5%, the mass proportion of the film-forming stabilizer is 0.1%, the mass proportion of the cationic clay is 1.5%, the mass proportion of the anionic clay is 2%, and the rest is made up of water. The super absorbent resin is sodium polyacrylate, the cationic clay is sodium bentonite, the film-forming stabilizer is anionic polyacrylamide, the anionic clay is aluminum-magnesium layered double metal hydroxide, and the water is deionized water.
[0086] The preparation method of the multi-network composite hydrogel inhibitor of this embodiment is the same as that of Example 1.
[0087] Embodiment 13
[0088] The multi-network composite hydrogel inhibitor includes a super absorbent resin, a film-forming stabilizer, a cationic clay, an anionic clay and an anti-hard water agent, wherein the mass proportion of the super absorbent resin is 0.5%, the mass proportion of the film-forming stabilizer is 0.05%, the mass proportion of the cationic clay is 1%, the mass proportion of the anionic clay is 0.6%, the mass proportion of the anti-hard water agent is 0.1%, and the rest is supplemented by water. Among them, the super absorbent resin is sodium polyacrylate, the cationic clay is sodium bentonite, the film-forming stabilizer is anionic polyacrylamide, the anionic clay is aluminum-magnesium layered double metal hydroxide, the anti-hard water agent is 2-acrylamide-2-methylpropane sulfonate sodium, and the water is artificial hard water with a hardness level of 10 (500 artificial hard water).
[0089] The preparation method of the multi-network composite hydrogel inhibitor of the present embodiment is as follows: solid materials and artificial hard water are weighed respectively according to the dosage ratio (mass fraction), the anti-hard water agent is first added to the artificial hard water and mixed evenly, and then the remaining solid materials are poured into the artificial hard water, stirred evenly and completely dispersed, and then allowed to stand for 24 hours to obtain the multi-network composite hydrogel inhibitor of the present embodiment, which is then pumped to a storage tank for standby use.
[0090] Comparative Example 1
[0091] The difference from Example 1 is that the mass proportion of the super absorbent resin is 0.01%.
[0092] Comparative Example 2
[0093] The difference from Example 1 is that the mass proportion of the super absorbent resin is 1%.
[0094] Comparative Example 3
[0095] The difference from Example 1 is that the mass proportion of the film-forming stabilizer is 0.01%.
[0096] Comparative Example 4
[0097] The difference from Example 1 is that the mass proportion of the film-forming stabilizer is 0.5%
[0098] Comparative Example 5
[0099] The difference from Example 1 is that the mass proportion of cationic clay is 0.1%.
[0100] Comparative Example 6
[0101] The difference from Example 1 is that the mass proportion of cationic clay is 3.0%.
[0102] Comparative Example 7
[0103] The difference from Example 4 is that the mass proportion of the anionic clay is 0.1%.
[0104] Comparative Example 8
[0105] The difference from Example 4 is that the mass proportion of anionic clay is 3%.
[0106] Comparative Example 9
[0107] The difference from Example 13 is that no anti-hard water agent is added.
[0108] Comparative Example 10
[0109] The inhibitor is composed of calcium chloride and deionized water, wherein the mass proportion of calcium chloride is 20% and the mass proportion of deionized water is 80%.
[0110] Comparative Example 11
[0111] The inhibitor consists of magnesium chloride and deionized water, wherein the mass proportion of magnesium chloride is 20% and the mass proportion of deionized water is 80%.
[0112] Test Example 1
[0113] The inhibitors of Examples 1 to 13 and Comparative Examples 1 to 11 were tested for their inhibitory rates and inhibitory lifespans. The test results are shown in Table 1.
[0114] The test method of the inhibition rate and the inhibition life is as follows: put the raw coal sample and the inhibited coal sample into the reaction tube respectively, put the reaction tube into the thermostat, and check the air tightness; turn on the CO detection device and preheat it; turn on the thermostat and heat it up at a rate of 1℃ / min; turn on the air pump and adjust the flow rate to let air in at a flow rate of 100mL / min; when the volume concentration of CO gas generated by the raw coal sample reaches 3×10 -6 When the temperature of the thermostat rises to (100±1)℃, the temperature is kept constant. When the CO volume concentration difference between the raw coal sample and the inhibited coal sample measured for 10 consecutive times changes less than 10%, and the resistance rate is less than 20%, the test is stopped. The corresponding time when the CO volume concentration difference between the raw coal sample and the inhibited coal sample changes less than 10% for the first time is the resistance rate time, and the time under the condition of 40% resistance rate is the resistance life.
[0115] The calculation formula of the resistance rate and resistance life is as follows:
[0116]
[0117] L=T n -T n-1 , n = 1, 2, 3
[0118] Where:
[0119] I is the resistance rate, the unit is percentage (%); V x is the volume of CO produced by the quenched coal sample, in cubic meters (m 3 );V y is the volume of CO produced by the raw coal sample, in cubic meters (m 3 );C n is the volume of the nth test point in the inhibited coal sample, in cubic meters (m 3 );C n ' is the volume of the nth test point in the raw coal sample, in cubic meters (m 3 ), i is the maximum number of measurements, and the parallelism error of the same sample is within ±3%.
[0120] L is the inhibitor life, in minutes (min); L xn T is the life of the inhibitor at a 40% inhibitory rate, in minutes (min); n It is the time when the nth inhibition rate reaches 40%, in minutes (min). The parallelism error of the inspection of the same sample is within ±3%.
[0121] Table 1:
[0122]
[0123]
[0124] According to Table 1, we can see that:
[0125] According to Examples 1 to 3, within a certain range, as the content of cationic clay increases, the resistance rate and resistance life of the composite hydrogel inhibitor increase; according to Examples 1 to 3 and Comparative Examples 5 and 6, when the content of cationic clay is too low or too high, the resistance rate and resistance life of the composite hydrogel inhibitor are significantly reduced. The reason is that when the content of cationic clay is too low, its synergistic water retention ability with the water-absorbing resin is poor, and after the water evaporates, it cannot effectively cover the surface of the coal body to form a protective layer, resulting in a decrease in the resistance rate and resistance life; when the content of cationic clay is too high, the system cannot be stably dispersed, and stratification will occur, resulting in a decrease in the resistance rate and resistance life of the composite hydrogel inhibitor.
[0126] According to Examples 4 to 6, within a certain range, as the content of anionic clay increases, the resistance rate and resistance life of the composite hydrogel inhibitor increase; according to Examples 4 to 6 and Comparative Examples 7 and 8, when the content of anionic clay is too low or too high, the resistance rate and resistance life of the composite hydrogel inhibitor are significantly reduced. The reason is that when the content of anionic clay is too low, its synergistic water retention ability with the water-absorbing resin is poor, and after the water evaporates, it cannot effectively cover the surface of the coal body to form a protective layer, resulting in a decrease in the resistance rate and resistance life; when the content of anionic clay is too high, the system cannot be stably dispersed, and stratification will occur, resulting in a decrease in the resistance rate and resistance life of the composite hydrogel inhibitor.
[0127] According to Examples 3, 7, and 8, within a certain range, as the content of the super absorbent resin increases, the resistance rate and resistance life of the composite hydrogel inhibitor increase; according to Examples 3, 7, and 8 and Comparative Examples 1 and 2, when the content of the super absorbent resin is too low or too high, the resistance rate and resistance life of the composite hydrogel inhibitor are significantly reduced. The reason is that when the content of the super absorbent resin is too high, it will cause it to agglomerate and agglomerate, affecting its water absorption and water retention properties, thereby reducing the resistance rate and resistance life; when the content of the super absorbent resin is too low, the components of the system cannot be evenly dispersed, resulting in a decrease in the resistance rate and resistance life of the composite hydrogel inhibitor.
[0128] According to Examples 3, 9, and 10, within a certain range, as the content of the film-forming stabilizer increases, it forms an associative hydrogen bond with the water-absorbing resin, so that the composite hydrogel system has a stronger water retention capacity, thereby increasing the resistance rate and resistance life of the composite hydrogel inhibitor; According to Examples 3, 9, and 10 and Comparative Examples 3 and 4, when the content of the film-forming stabilizer is too low or too high, the resistance rate and resistance life of the composite hydrogel inhibitor are significantly reduced. The reason is that when the content of the film-forming stabilizer is too high, the dispersibility of the composite hydrogel system will be deteriorated, thereby causing the resistance rate and resistance life to decrease; when the content of the film-forming stabilizer is too low, the adhesion of the inhibitor is poor and it cannot adhere to the coal wall, thereby causing the resistance rate and resistance life of the composite hydrogel inhibitor to decrease.
[0129] According to Example 13 and Comparative Example 9, when hard water is used to prepare the composite hydrogel inhibitor, the use of the anti-hard water agent improves the inhibition rate and the inhibition life of the composite hydrogel system.
[0130] According to Examples 1 to 13, namely Comparative Examples 10 and 11, it can be seen that the inhibition rate and the inhibition life of the composite hydrogel inhibitor proposed by the present invention are better than those of the existing magnesium chloride and calcium chloride inhibitors.
[0131] Test Example 2
[0132] The flame retardant performance of the inhibitors and coal powder of Examples 1 to 13 and Comparative Examples 1 to 11 was tested. The test results are shown in Table 2 below.
[0133] Among them, the flame retardant performance test method is: use a cone calorimeter to test the flame retardant performance, prepare the raw coal sample and the inhibitor into samples with a size of 100mm×100mm and a thickness of ≤50mm for testing, carry out ignition test under the condition of radiation intensity of 50kW / ㎡, and record relevant data.
[0134] Table 2:
[0135]
[0136]
[0137] According to Table 2, we can see that:
[0138] Within a certain range, an increase in the content of cationic clay or anionic clay will prolong the ignition time of the sample, reduce the average heat release rate of 180s and 300s, and reduce the total smoke production per unit area. However, when the content of cationic clay or anionic clay is too high or too low, it will affect the water retention capacity of the water-absorbing resin, thereby shortening the ignition time of the system and affecting the heat release rate.
[0139] Within a certain range, increasing the content of water-absorbing resin or film-forming stabilizer will make the composite hydrogel system more capable of retaining water, thereby extending the ignition time, reducing the average heat release rate and smoke production per unit area. However, too high or too low a content of water-absorbing resin or film-forming stabilizer will reduce the ignition time of the system, increase the heat release rate and smoke production per unit area.
[0140] When hard water is used to prepare the composite hydrogel inhibitor, the addition of the anti-hard water agent will prolong the ignition time of the composite hydrogel system and reduce the average heat release rate and smoke production per unit time.
[0141] The flame retardant performance of the multi-network composite hydrogel inhibitor proposed by the invention is better than that of the existing magnesium chloride and calcium chloride inhibitors.
[0142] Use effect verification:
[0143] For the mine water quality with water hardness of 400 or less, the 8701 fully mechanized mining face with a length of 260m and a height of 8m, and a daily progress of 6m / day, the spraying amount of Example 1 is 50m 3 / day, and observe and test the spraying situation and carbon monoxide concentration in the goaf for 48 hours. The gel inhibitor is attached to the wall of the goaf. The carbon monoxide concentration is 2ppm before spraying and 0ppm after spraying. The carbon monoxide concentration is qualified and there is no irritating odor.
[0144] For the mine water quality with a water hardness of 400 or above, the 8701 fully mechanized mining face with a length of 260m and a height of 8m, and a daily progress of 6m / day, the spraying amount of Example 2 is 50m 3 / day, and observe and test the spraying situation and carbon monoxide concentration in the goaf for 48 hours. The gel inhibitor is attached to the wall of the goaf. The carbon monoxide concentration is 2ppm before spraying and 1ppm after spraying. The carbon monoxide concentration is qualified and there is no irritating odor.
[0145] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0146] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0147] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A multi-network composite hydrogel inhibitor, characterized in that: include: Highly water-absorbent resin, the mass proportion of the highly water-absorbent resin in the inhibitor is 0.3% to 0.8%; A film-forming stabilizer, wherein the mass proportion of the film-forming stabilizer in the inhibitor is 0.05% to 0.2%; Cationic clay and / or anionic clay, wherein the mass proportion of the cationic clay in the inhibitor is 0.6% to 2%, and the mass proportion of the anionic clay in the inhibitor is 0.6% to 2%.
2. The inhibitor according to claim 1, characterized in that It also includes an anti-hard water agent, and the mass proportion of the anti-hard water agent in the inhibitor is less than 0.1%.
3. The inhibitor according to claim 1, characterized in that The anti-hard water agent includes one or more of 2-acrylamide-2-methylpropane sulfonate sodium, 3-(N-morpholine)-propane sulfonate sodium and polymers thereof.
4. The inhibitor according to claim 1, characterized in that The highly water-absorbent resin includes one or more of polyacrylic acid, sodium polyacrylate, and polypropylene alcohol.
5. The inhibitor according to claim 1, characterized in that The film-forming stabilizer includes one or more of anionic polyacrylamide, cationic polyacrylamide, and nonionic polyacrylamide.
6. The inhibitor according to claim 1, characterized in that The cationic clay includes one or more of sodium bentonite, calcium bentonite and organic bentonite.
7. The inhibitor according to claim 1, characterized in that The anionic clay includes one or both of aluminum-magnesium layered double metal hydroxide and hydrophilically modified aluminum-magnesium layered double metal hydroxide.
8. A method for preparing an inhibitor, characterized in that: The method for preparing the inhibitor according to any one of claims 1 to 7 comprises the following steps: Weigh solid materials respectively according to the usage ratio, and mix the solid materials evenly to obtain a mixture; The mixture is added into deionized water or hard water containing an anti-hard water agent, stirred until completely dispersed, and then allowed to stand to obtain a multi-network composite hydrogel inhibitor.
9. The preparation method according to claim 8, characterized in that: The solid material comprises at least one of cationic clay and anionic clay, a highly absorbent resin and a film-forming stabilizer.
10. Use of the inhibitor according to any one of claims 1 to 7 or the inhibitor prepared by the method according to claim 8 or 9 in the prevention and control of spontaneous combustion in coal mines.